Case Report: Prenatal Whole-Exome Sequencing Identified a Novel Nonsense Mutation of the KCNH2 Gene in a Fetus With Familial 2q14.2 Duplication - Zhuang, Jianlong; Chen, Chunnuan; Wang, Yuanbai; Zeng, Shuhong; Chen, Yu’e; Jiang, Yuying; Xie, Yingjun; Wang, Gaoxiong (Frontiers in Genetics, 2022)
Background: Pathogenic mutations in the KCNH2 gene were associated with long QT syndrome 2 (LQT2), which typically manifest in a prolonged QT interval and may lead to recurrent syncopes, seizure, or sudden death. Limited reports indicated that the KCNH2 mutations would result in LQT2 combined with tetralogy of fallot. Our goal was to present an additional case of LQT2 combined with the tetralogy of fallot in a fetus with a novel KCNH2 mutation. Case presentation: Enrolled in this study was a 23-year-old pregnant woman from Quanzhou Fujian province, China. In her pregnancy, fetal ultrasound anomalies were identified, including tetralogy of fallot, coronary sinus enlargement, and persistent left superior vena cava. No chromosomal abnormality was detected by fetal karyotype analysis. However, 238.1-kb duplication in the 2q14.2 region containing the GLI2 gene was observed in the fetus by chromosomal array analysis, which was inherited from the mother with normal clinical features and interpreted as a variant of uncertain significance (VOUS). Furthermore, whole-exome sequencing (WES) detection identified a novel nonsense c.1907C > G (p.S636*) mutation in the KCNH2 gene in the fetus, and it was classified as a likely pathogenic variant, according to the ACMG guidelines. Parental verification analysis indicated that c.1907C > G (p.S636*) mutation was inherited from the mother. Conclusion: In this study, we believe that 2q14.2 duplication may not be the reason for fetal heart defects; moreover, we described an additional case with KCNH2 gene mutation, which may lead to LQTS and be associated with congenital heart defects. In addition, our study further confirms the application value of the WES technology in prenatal genetic etiology diagnosis of fetuses with structural anomalies and unexplained structural variants.